An extended fuzzy TOPSIS-GRA method based on different separation measures for green logistics service provider selection - Celik, E.; Erdogan, M.; Gumus, A. T. (SPRINGER, 2016)
In this paper, first, the criteria that make logistics service providers more green'' are determined as: cooperation with customer's company and its customer, green government regulations, environmental management system, green process design, reduction in energy consumption and green network design. The criteria weights are determined by fuzzy AHP, based on expert opinions. Then, a new method is proposed, which is the combination of fuzzy TOPSIS and GRA, and used to evaluate green 3PLs based on different separation measures, as an extension, using trapezoidal fuzzy numbers. Five Turkish 3PLs serve in Istanbul are selected in order to apply a case study to show the applicability of the proposed method. Finally, the proposed method is verified with respect to different resolving coefficient values and separation measures and also compared with fuzzy TOPSIS and fuzzy VIKOR method results. Different multi-criteria decision-making methods can be applied and compared to check validity of our results for future studies. The proposed method can also be implemented to 3PLs in other countries.
Keywords: Fuzzy GRA; Fuzzy TOPSIS; Green logistics; Logistics service provider selection; Trapezoidal fuzzy numbers; GROUP DECISION-MAKING; SUPPLIER SELECTION; ENVIRONMENTAL CRITERIA; PERFORMANCE; INTEGRATION; MANAGEMENT; NETWORK; MODEL; ANP; 3PL; Environmental Sciences & Ecology